Digital agency: Empowering farmers to co-create knowledge on agroecology practices - McCampbell, Mariette; Dittmer, Kyle Michael; Shelton, Sadie; Wollenberg, Eva (2025)
KEY MESSAGES - Digital tools are an increasingly common approach to providing agricultural advisories, yet often many farmers do not participate in digital knowledge systems. - Conventional approaches for analyzing digital inclusion focus on internet access, digital literacy, and benefit inequalities, and overlook agroecology values such as co-creation of knowledge, agency, and empowerment. - Co-creation of knowledge is a continuous process in which those participating need to have real influence. If not, the power stays with the technology developers. - Combining knowledge that is co-created by many diverse people and data and information from digital tools leads to responsible hybrid collective intelligence. - Features of digital tools that support co-creation of knowledge, digital agency, and scaling of agroecology practices include that they enable knowledge integration, two-way communication, inclusive access, and responsible use. - A step-wise approach is needed to develop digital resources that enable farmers’ digital agency and support the scaling of agroecological practices.